Pengaruh Bullying Terhadap Perkembangan Mental Generasi Muda - Umam, Hafidzl Katibul; Mutiara, Citra; Nurmala, Sany (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2024)
The influence of bullying on the mental development of the younger generation has a very serious impact on the physical and psychological, the impact resulting from this act of bullying greatly influences the development of growth and development and the future is at risk. The aim of this research is to find out what impact bullying has on the mental development of the younger generation at SMAN 2 Cimahi, and to find out what efforts all elements of society have made to prevent and minimize bullying. This research uses a quantitative approach in the form of a questionnaire aimed at SMAN 2 Cimahi students regarding the influence of bullying. This research produces an understanding and insight into bullying and its impact on the survival of generations. This research contributes to becoming a reference for all elements of society in understanding what bullying is and understanding efforts to prevent and minimize bullying from as early as possible